2020
DOI: 10.3390/agriculture10080343
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Indole-3-Acetic Acid Concentration in a Nutrient Solution for Increasing Bioactive Compound Accumulation and Production of Agastache rugosa in a Plant Factory

Abstract: This study aimed to determine the optimal indole-3-acetic acid (IAA) concentration in a nutrient solution to increase the bioactive compounds while enhancing the plant growth of A. rugosa grown hydroponically. Twenty-eight-day-old plants were transplanted in a plant factory for 32 days. The plants were subjected to various IAA concentrations (10−11, 10−9, 10−7, and 10−5 M) from 8 days after transplanting, and the control treatment (without IAA). Shoot and root fresh weights were effectively improved under 10−7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The ability of DPM17 to produce growth regulators (IAA and gibberellins) also confirms its plant-stimulation capability. IAA is a plant hormone that improves seed germination and the growth of different plant organs even at 10 −9 -10 −12 M [35,36]. In this study, DPM17 produced 5.04 µg mL −1 IAA, which is similar to that produced by Bacillus sp.…”
Section: Discussionsupporting
confidence: 58%
“…The ability of DPM17 to produce growth regulators (IAA and gibberellins) also confirms its plant-stimulation capability. IAA is a plant hormone that improves seed germination and the growth of different plant organs even at 10 −9 -10 −12 M [35,36]. In this study, DPM17 produced 5.04 µg mL −1 IAA, which is similar to that produced by Bacillus sp.…”
Section: Discussionsupporting
confidence: 58%
“…Many studies have reported that EC levels of nutrient solutions affect the growth of various crops [19,20,33]. In our study, most of the growth characteristics of red perilla decreased as the EC levels increased, and NSP 1 dS m −1 showed the highest values compared with other EC levels of CT and NSP, which implies that NSP 1 dS m −1 was appropriate for the growth of red perilla.…”
Section: Growth Characteristicssupporting
confidence: 54%
“…The total phenolic, RA, and CA concentration of red perilla increased as the EC levels increased, which showed an opposite trend to growth characteristics. In contrast, previous studies reported that a low-nutrient solution increased the RA content in green and red perilla, Prunella vulgaris, and Agastache rugosa [20,33,49]. The deficiency of some minerals, such as nitrogen, phosphorus, and potassium, causes a decrease in the phenolic contents of crops [50].…”
Section: Biochemical Parametersmentioning
confidence: 90%
See 1 more Smart Citation
“…IAA stimulates root and stem development, lateral root initiation, root elongation by increasing cell division and extension (Lam et al, 2020). The tomato plants subjected to this research were at the mature stage (25 days) and the fruiting stage (50 days).…”
Section: Discussionmentioning
confidence: 99%